Integrated Trauma-Focused Cognitive-Behavioural Therapy for Post-traumatic Stress and Psychotic Symptoms: A Case-Series Study Using Imaginal Reprocessing Strategies - Keen, Nadine; Hunter, Elaine C. M.; Peters, Emmanuelle (Frontiers in Psychiatry, 2017)
Despite high rates of trauma in individuals with psychotic symptoms, post-traumatic stress symptoms are frequently overlooked in clinical practice. There is also reluctance to treat post-traumatic symptoms, in case the therapeutic procedure of reprocessing the trauma exacerbates psychotic symptoms. Recent evidence demonstrates that it is safe to use reprocessing strategies in this population. However, most published studies have been based on treating post-traumatic symptoms in isolation from psychotic symptoms. The aims of the current case series were to assess the acceptability, feasibility and preliminary effectiveness of integrating cognitive-behavioural approaches for post-traumatic stress and psychotic symptoms into a single protocol. Nine participants reporting distressing psychotic and post-traumatic symptoms were recruited from a specialist psychological therapies service for psychosis. Clients were assessed at five time points (baseline, pre-, mid, end of therapy and at 6+ months follow-up) by an independent assessor on measures of current symptoms of psychosis, post-traumatic stress, emotional problems and well-being. Therapy was formulation-based and individualised, depending on presenting symptoms and trauma type. It consisted of five broad, flexible phases, and included imaginal reprocessing strategies (reliving and/or rescripting). The intervention was well received, with positive post-therapy feedback and satisfaction ratings. Unusually for this population, no-one dropped out of therapy. Post-therapy, all but one (88% of participants) achieved a reliable improvement compared to pre-therapy on at least one outcome measure: post-traumatic symptoms (63%), voices (25%), delusions (50%), depression (50%), anxiety (36%) and well-being (40%). Follow-up assessments were completed by 78% (n=7), 86% (n=6) of whom maintained at least one reliable improvement. Rates of improvements following therapy (average of 44% across measures post-therapy; 32% at follow-up) were over twice those found during the waiting list period (19%). No participant indicated a reliable worsening of any symptoms during or after therapy. The study shows that an integrative therapy incorporating reprocessing strategies was an acceptable and feasible intervention for this small sample, with promising effectiveness. A randomised controlled trial is warranted to test the efficacy of the intervention for this population.